Family estimates of risk for neurocognitive late effects following pediatric cancer: From diagnosis through the first three years of survivorship. Issue 9 (25th January 2017) - Shultz, Emily L.; Lehmann, Vicky; Rausch, Joseph R.; Keim, Madelaine C.; Winning, Adrien M.; Olshefski, Randal S.; Vannatta, Kathryn A.; Compas, Bruce E.; Gerhardt, Cynthia A.
Abstract: Background: Families often express a need for additional information about neurocognitive late effects (NCLE) after a pediatric cancer diagnosis. Therefore, we examined: (i) differences in parent, child, and oncologist estimates of risk for NCLE; (ii) whether the estimates of parents and/or children change over time; and (iii) whether estimates are different for children treated with central nervous system (CNS) directed therapies. Procedure: Mothers, fathers, and children (initial age: 5–17, self‐report: >10) from 258 families reported their perceived likelihood of the child developing "thinking/learning problems" on a visual analog scale (0–100%) at 2 months (T1), 1 year (T2), and 3 years (T3) following cancer diagnosis/relapse. Oncologists estimated the likelihood of NCLE at T1. Children were separated into groups based on CNS‐directed treatment (n = 137; neurosurgery, intrathecal chemotherapy, and/or craniospinal radiation) or no CNS treatment. Results: Mother, father, and child estimates of risk for NCLE were similar to oncologists and to one another around diagnosis (T1). Although there were no significant mean differences, a considerable subset of family members either underestimated their child's risk for NCLE (>40%) or overestimated the risk for NCLE (20%) in comparison to oncologists. At T2 and T3, the estimates of mothers were significantly higher than children. Linear growth curves indicated that mothers' estimates for children with CNS‐directed treatment significantly increased throughout the first 3 years of survivorship. Conclusions: Considering that accurate understanding of NCLE is essential to seeking appropriate assessment and intervention, healthcare providers should focus on implementing family‐based education early in treatment and throughout survivorship care.